HUBUNGAN ANTARA BURNOUT DENGAN SELF EFFICACY PADA PERAWAT DI PUSKESMAS TAMAN KECAMATAN TAMAN KROCOK KABUPATEN BONDOWSO - Sri Ummi (Lembaga Penelitian dan Pengabdian Masyarakat Universitas dr. Soebandi, 2018)
Nurses are responsible professionals and are authorized to provide nursing independently or collaborate with other health professionals, being a nurse having complex tasks and nurses in direct contact with patients. This study aims to determine the relationship between burnout and self-efficacy in nurses in Taman krocok Puskesmas Bondowoso Regency. The design of this study uses the correlation design using a cross sectional survey method number of samples 10 sampling techniques total sampling Data collection tools using a closed questionnaire. Spearman Rho Chorrelation statistical test with significance level p <0.05 where Ha is accepted and Ho is rejected. The results showed that a high burnout rate was 40%, a moderate burnout rate was 20%, low self efficacy was 40% and self efficacy was less than 20%. Spearman Rho Chorrelation statistical test produced a correlation coefficient r = -980 with a significance value of p = .000. These results indicate there is a relationship between burnout with self efficacy in nurses in Taman Krocok Health Center, Taman Krocok District, Bondowoso Regency. It is expected that from this study nurses increase self-efficacy so they do not experience burnout